Ruthenium(II) 2,2′-bipyridyl tetrakis acetonitrile undergoes selective axial photocleavage - Petroni, Agustín (2008)
The complex [Ru(bpy)(AN)4]2+ (bpy = 2,2′-bipyridyl, AN = acetonitrile) has a Ru(II) → π*bpy MLCT band at 388 nm. Upon irradiation on this absorption band, the compound undergoes total regioselective photocleavage yielding complexes fac-[Ru(bpy)(AN)3(H2O)]2+ and trans-[Ru(bpy)(AN)2(H2O)2]2+ in two consecutive steps with quantum yields of 0.43 and 0.09, respectively. This behavior is a consequence of the stronger σ-donor ability of the bpy nitrogens that determines the orbital ordering and therefore the nature of the lowest lying 3d-d state responsible for the photochemistry. The two-step photoreaction, which can be followed by UV-vis and NMR spectra, provides a quantitative path to the preparation of trans-polypyridine species with potentially interesting photochemical properties.